News Agengies and Global News Flow in the 21st Century - Nwokeocha Ifeanyi Martins (CV. Rayyan Dwi Bharata, 2022)
News flow controversies have continued to dominate discussions on international communication. A lot of factors account for the lopsided flow of global information. One of such factors bothers on the role news agencies (otherwise called wire services) play in global information dissemination. The influence of news agencies on global news circulation can never be over emphasized. This simply implies that wire services, being suppliers of news choose what to supply, why to supply and how to supply. And often times the answers of these 5Ws and H of news agencies dissemination of global news tilt towards or favours the owners, the financiers, the location or areas of domicile-the West. News agencies have continued to improve in their quest to saturate the entire globe with up-to-the- minute information. To achieve this, a myriad of techniques and technologies have been employed. This article examines the influence of news agencies on global news flow in the 21st century. It highlights how the location of the largest wire services brings about imbalance in the flow of global mass communication.